Analisis PIECES terhadap E-Commerce Produk Daur Ulang pada Bank Sampah Jayapura - Muhammad Taher Jufri; Jusmawati; Kartini Darma Waromi (Jurnal Sistim Informasi dan Teknologi, 2022)
The system in the process of marketing transactions, sales and purchases of recycled products made by women is centered at the Jayapura Waste Bank. This centralized system has the effect of being less well known by the public. This system is also still weak in promotion, either through print or social media. Promotion only takes place from customers who have purchased products at this bank. In addition, there is no means of purchasing and paying online. So this research was conducted with the aim of building an online system by applying the waterfall method, data collection method, PIECES analysis method, UML design method and black box testing method. The result of this research is an online system in the form of e-Commerce Recycled Products at the Jayapura Waste Bank. These results make it easier to get reliable mobile-based marketing, sales, and purchase transaction process for recycled products. So that this system can be used as a reference in building a waste bank.